Bluetooth indoor location determination system using heuristic approach - Alimozzaman, Deawn Md. (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.